Climatic variables and altitude as predictors of anuran species richness and number of reproductive modes in Brazil - Vasconcelos, Tiago Da Silveira [UNESP]; Santos, Tiago Gomes Dos [UNESP]; Haddad, Célio Fernando Baptista [UNESP]; Rossa-Feres, Denise de Cerqueira [UNESP] (Cambridge University Press (CUP), 2010)
Because anuran species are highly dependent on environmental variables, we hypothesized that anuran species richness and the number of reproductive modes from different Brazilian localities vary according to climatic and altitudinal variables. Published data were compiled from 36 Brazilian localities and climatic and altitudinal data were extracted from an available database. A partial redundancy analysis (pRDA) showed that 23.5% of the data set's variation was explained by climatic and altitudinal data, while the remaining 76.5% remained unexplained. This analysis suggests that other factors not analysed herein may also be important for predicting anuran species richness and the number of reproductive modes in Brazil. Altitude and total annual rainfall were positively correlated with anuran species richness and the number of reproductive modes, and total annual rainfall was strongly associated with these two biotic variables in the triplot of pRDA. The positive association of total annual rainfall and the negative association of the concentration of annual rainfall were already expected based on physiological and reproductive requirements of anurans. On the other hand, temperature was not associated with richness or the number of reproductive modes. Copyright © 2010 Cambridge University Press.
Keywords: Amphibia; Brazilian biomes; climatic effects; herpetology; meta-analysis; redundancy analysis; altitude; amphibian; climate effect; data set; environmental factor; precipitation (climatology); reproductive biology; species richness; statistical application; Brazil; Anura